2014
DOI: 10.1080/02640414.2014.970218
|View full text |Cite
|
Sign up to set email alerts
|

From childhood to senior professional football: elite youth players’ engagement in non-football activities

Abstract: Despite the large amount of research available on how engagement in football practice relates to future performance level among football players, similar information about the contribution of non-football activities is scarce. Based on data from 745 elite youth players this study aimed to identify the characteristics and contribution of diverse participation towards elite youth and senior professional status. The data were collected using a retrospective questionnaire where the players reported the amount of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…A more recent study using Portuguese futsal players reported that elite players dedicated themselves to the sport earlier than their non-elite counterparts (Serrano, Santos, Sampaio, & Leite, 2013). These results are in conflict with an investigation that assessed the contribution of diverse participation towards the attainment of elite youth and senior professional status in soccer players (Haugaasen, Toering, & Jordet, 2014). A retrospective questionnaire was utilised and reported the amount of time spent partaking in sports other than soccer and their perceived contribution of non-soccer related activities.…”
Section: Introductioncontrasting
confidence: 86%
“…A more recent study using Portuguese futsal players reported that elite players dedicated themselves to the sport earlier than their non-elite counterparts (Serrano, Santos, Sampaio, & Leite, 2013). These results are in conflict with an investigation that assessed the contribution of diverse participation towards the attainment of elite youth and senior professional status in soccer players (Haugaasen, Toering, & Jordet, 2014). A retrospective questionnaire was utilised and reported the amount of time spent partaking in sports other than soccer and their perceived contribution of non-soccer related activities.…”
Section: Introductioncontrasting
confidence: 86%
“…It is now commonplace for youth athletes to engage with a variety of physical preparation modalities as part of their sporting development. Moreover, physical competency and capacity of senior athletes has been associated with early exposure to physical development opportunities throughout childhood and adolescence (Gonaus & Müller, 2012;Haugaasen, Toering, & Jordet, 2014). However, the body of literature surrounding adolescent athletes has historically been scarce comparative to adults.…”
Section: Sir Alex Ferguson (2013)mentioning
confidence: 99%
“…As a result of their early success and feedback that identifi es them as talented, the talented players are also expected to be solely focused on their main sport, potentially increasing the diff erence in skills compared to less talented peers and, furthermore, increasing the players' ambitions (Saether, 2013) to become potential professional players. With regard to the number of sports in which players had participated, results from earlier studies indicate that there were no diff erences between players obtaining a senior professional contract and non-professional players (Haugaasen, Toering, & Jordet, 2014b), as was also shown in other similar studies (Ford et al, 2012). Later research has also shown that the amount of training cannot be taken as a predictor of future success since players obtaining a senior professional contract were not found to train more than non-professional players in their youth (Haugaasen, Toering, & Jordet, 2014a).…”
Section: Characteristics Of Professional and Non-professional Footbalmentioning
confidence: 99%